Proposal of an economic dependence index for smaller areas and its application to the Metropolitan Region of Buenos Aires, Argentina (2010) - Manzano, Fernando Ariel; Velázquez, Guillermo Ángel (Pontifícia Universidade Católica de São Paulo, 2019)
The most used measure of the load of demographic dependence is the relation of demographic dependence. This index lacks theoretical support and is based on a purely biological criterion. The objective is to generate an alternative index to estimate the load of economic dependence from a multidimensional theoretical perspective that adjusts to spatial inequalities and, in the theoretical field, admits the existence of a diffuse link between demography and economy, as well as the lack of a consensus concerning economic growth determinants and the creation of employment. The application of the alternative index is constructed for a disaggregation level corresponding to the census fraction for the Metropolitan Region of Buenos Aires in 2010.